Headspace analysis of volatile metabolites of Pseudomonas aeruginosa and related species by gas chromatography-mass spectrometry. - Labows, J N (1980)
Gas chromatographic-mass spectrometric analysis of headspace volatiles was performed on cultures of 11 strains of Pseudomonas aeruginosa and 1 strain each of Pseudomonas cepacia, Pseudomonas putida, Pseudomonas putrefaciens, Pseudomonas fluorescens, and Pseudomonas maltophilia. All strains of Pseudomonas aeruginosa produced a distinctive series of odd-carbon methyl ketones, particularly 2-nonanone and 2-undecanone, and 2-aminoacetophenone. The other strains failed to produce 2-aminoacetophenone. Two sulfur compounds, dimethyldisulfide and dimethyltrisulfide, were present in strains of P. aeruginosa and in variable amounts in other species. Butanol, 2-butanone, 1-undecene, and isopentanol were also detected in P. aeruginosa cultures.